On-line coupling of solid-phase extraction with mass spectrometry for the analysis of biological samples: III. Determination of prednisolone in serum - van Hout, M.W.J; Hofland, C.M; Niederländer, H.A.G; Bruins, A.P; de Zeeuw, R.A; de Jong, G.J (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2003)
Solid-phase extraction (SPE) was directly coupled to mass spectrometry (MS) to assess the feasibility of the system for the rapid determination of prednisolone in serum. A C 18 stationary phase allowed washing of the cartridge with 25% methanol. Elution was performed by switching the methanol percentage from 25% in the washing step to 50% during elution. The high flow-rates during the extraction (5.0 ml/min) combined with ion-trap MS detection resulted in a total analysis time of 4 min. Some tailing of the prednisolone peak was observed. However, the tailing was found acceptable, since by this elution procedure most matrix compounds were prevented from eluting from the cartridge. Some matrix interference was still observed with a triple-quadrupole MS, even in the multiple reaction monitoring mode. This resulted in a detection limit (LOD) of about 10 ng/ml. The matrix interference and the LOD were similar for atmospheric pressure chemical ionisation and atmospheric pressure photo ionisation. Applying an ion-trap MS in the MS–MS mode resulted in cleaner chromatograms. Due to extensive fragmentation of prednisolone, the LOD was not lower than about 5 ng/ml prednisolone in serum, and a limit of quantitation of about 10 ng/ml (relative standard deviation <15%) was observed.